Urban hierarchy and spatial interaction in the regional urban system in Dobrogea, Romania - Matei, Gheorghe (Journal for Geography, 2024)
A region has a certain area within which there is a certain number of cities that are different in the number of the inhabitants, located at different distances from each other, forming an urban system that is based on the multitude of relationships between them. This study investigates the hierarchy of the 16 cities that make up the regional urban system of Dobrogea, as well as the spatial interaction between them. To achieve these goals, several models were used, such as those of Zipf, Beckman, and Reilly-Converse, and the Jefferson index. The results of the study indicate the urban primacy (hypertophy) of the largest city in the territory located between the Danube and the Black Sea, Constanța, as well as the macrocephaly of its regional urban system. Zipf’s law shows the incoherence, the imbalance of the urban system and divides its cities into plethoric cities and deficit cities. The same characteristics of the urban system are also confirmed by Beckman’s law. By applying the Reilly-Converse law, the zone of influence of the city of Constanța was delimited, almost 38% of the entire area of the Dobrogea region.